How to Conﬁgure Row-Sampling-Based Rowhammer Defenses - Saroiu, Stefan; Wolman, Alec (2nd Workshop on DRAM Security (DRAMSec), 2022)
Row-Sampling is a simple, practical, and strong form of Rowhammer defense if properly conﬁgured. Unfortunately, previous papers either omit describing how to conﬁgure Row-Sampling, or when they do, their formulae suffer from limitations and unrealistic assumptions. This paper presents a mathematically rigorous description of how to conﬁgure Row-Sampling to protect an entire system for a given period of time